Nutritional properties of edible bird nest - Zainab, Hamzah, Prof. Madya Dr.; Nur Hulwani, Ibrahim; Jeyaraman, Sarojini; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Othman, Hashim, Prof. Madya Dr.; Lee, Boon Beng (Asian Economic and Social Society, 2013)
Link to publisher's homepage at http://www.aessweb.com/